Caracterização da fibra da planta Agave angustifolia var. marginata para aplicação em compósitos de poliéster - Silva, Roseméri Barbosa dos Santos da (2023)
The use of lignocellulosic fibers (natural fibers) has beenwidely investigated as a reinforcement material in polymeric composites because it presents characteristics of biodegradability, low cost, low density and mechanical properties relevant to the replacement of synthetic fibers. In the present study, lignocellulosic fibers of Agave angustifolia var. marginata (AAM) were characterized in order to evaluate their potential as a reinforcement material and their influence on unsaturated polyester matrix composites. Thus, X-ray diffractometry (DR-X) and Fourier transform (FT-IR) spectroscopy, thermogravimetry, diametral distribution, fiber traction test and scanning electron microscopy (SEM) were performed. The application of long fibers as reinforcement material in the unsaturated polyester matrix was evaluated for proportions of 10, 20 and 30% by weight in a guided way. The properties of the composites developed for the different fiber contents of A. angustifolia var. marginata (FAAM) were investigated in order to analyze the interactions between fiber and matrix, thermal stability, mechanical properties, SEM of the fracture surface and resistance to water absorption. It was found that the addition of FAAM in the polyester matrix provided significant improvements in the mechanical properties of traction and impact. It was observed that with the addition of 10%, 20% and 30% by weight of FAAM in the polyester matrix the average strength of the composites had an increase of 56%, 180% and 293%, respectively. The thermal stability and moisture resistance of the reinforced composites were lower compared to polyester. The scanning electron microscopy (SEM) analysis showed that there was a good adhesion between fiber and matrix, in which they acted as effective barriers preventing and diverting the cracks of the matrix, and as an effect increased the absorbed impact energy and the tensile strength of the composites. Thus, the results found in this study indicate that the natural fibers of AAM exhibit reinforcement characteristics for application in polymeric composites.